2018
DOI: 10.1111/nph.15353
|View full text |Cite
|
Sign up to set email alerts
|

STAYGREEN, STAY HEALTHY: a loss‐of‐susceptibility mutation in the STAYGREEN gene provides durable, broad‐spectrum disease resistances for over 50 years of US cucumber production

Abstract: The Gy14 cucumber (Cucumis sativus) is resistant to oomyceteous downy mildew (DM), bacterial angular leaf spot (ALS) and fungal anthracnose (AR) pathogens, but the underlying molecular mechanisms are unknown. Quantitative trait locus (QTL) mapping for the disease resistances in Gy14 and further map-based cloning identified a candidate gene for the resistant loci, which was validated and functionally characterized by spatial-temporal gene expression profiling, allelic diversity and phylogenetic analysis, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 96 publications
(150 reference statements)
1
68
0
Order By: Relevance
“…reported that dm5.1, dm5.2, and dm5.3 were major-effect QTLs contributing to DM resistance. Wang et al (2019) identi ed a DM resistance gene STAYGREEN, which also located on Chr5 [12]. Therefore, we proposed that the sites located on Chr5 was the most likely loci on DM resistance.…”
Section: Downy Mildew (Dm) Is Caused By the Obligate Biotrophic Oomycmentioning
confidence: 96%
See 1 more Smart Citation
“…reported that dm5.1, dm5.2, and dm5.3 were major-effect QTLs contributing to DM resistance. Wang et al (2019) identi ed a DM resistance gene STAYGREEN, which also located on Chr5 [12]. Therefore, we proposed that the sites located on Chr5 was the most likely loci on DM resistance.…”
Section: Downy Mildew (Dm) Is Caused By the Obligate Biotrophic Oomycmentioning
confidence: 96%
“…Downy mildew was also devastating in cucumber. Many researches on downy mildew in cucumber have been reported [10][11][12]. Zhang et al (2013) constructed the F 2 and F 2:3 population based on the cross of inbred line K8 and K18 and identi ed 5 QTLs (dm1.1, dm5.1, dm5.2, dm5.3 and dm6.1) associated with DM on the Chr1, Chr5 and Chr6, respectively.…”
Section: Downy Mildew (Dm) Is Caused By the Obligate Biotrophic Oomycmentioning
confidence: 99%
“…The clustering of R-genes is an evolutionarily conserved defense mechanism in plants wherein recombination in closely located genes creates new motif combinations, which generates novel resistance speci cities and broadens plant resistance to different diseases [42,64]. R-gene clusters that provide resistance to multiple diseases have been reported for angular leaf spot, downy mildew, and anthracnose diseases in cucumber [65] and for blackleg, sclerotinia stem rot, and clubroot diseases in B. napus [66][67][68] and B. rapa [66]. In melon, a 1 Mb region on chromosome ve contains the highest density of R-genes [69].…”
Section: Discussionmentioning
confidence: 99%
“…The genomic DNA sequence diversity of the 50 kb F locus was examined in 48 re-sequenced cucumbers lines reported previously 86,87 and the three 'gynoecy loss' mutants. SNPs within the target region were called with the BWA-GATK4.0 workflow using 9930 V2.0 as the reference following Wang et al 88 . All detected polymorphisms (SNPs or InDels) in the 30-kb CNV sequence in the 'gynoecy loss' mutants were verified by PCR and Sanger sequencing.…”
Section: Genome Structure Analysis At F Locusmentioning
confidence: 99%